Concept Mapping Model, Academic Disciplines and Interdisciplinarity - McAlpine, Steven (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
Why do we use maps? What sense of understanding does a map provide that a simple list of directions cannot? Beginning with an examination of the most useful properties of maps, we will then review a methodology for constructing a conceptual map used to explore the complexities of a topic or problem. DOI: http://dx.doi.org/10.3126/ctbijis.v2i1.10808 Crossing the Border: International Journal of Interdisciplinary Studies Vol.2(1) 2014: 7-12